Serum Concentration of Molybdenum in Chronic Renal Failure Patients Requiring Hemodialysis - Manuti, Jawad K.; Al-Rubaye, Faisal Gh.; Khudhair, Mahmood S. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: High serum molybdenum level may contribute to dialysis related bone disease in patients requiring long term hemodialysis in fact massive molybdenum accumulation causes joint deformity and arthritis Objective: To asses the level of molybdenum in uremic patients requiring long term hemodialysis and impact of hemodialysis on the serum level of molybdenum before and after hemodialysis Patients and methods: Eighty patients complain from chronic renal failure on long term hemodialysis aged (16 to 65) years, serum molybdenum was measured before and after hemodialysis Result: The mean serum molybdenum level in 80 patients requiring long term hemodialysis was elevated before dialysis (0.29 + 0.17 nmol/mL) and even after dialysis (0.16 + 0.05 nmol/mL) in comparison to the normal value (normal 0.02——0.13 nmol/ml).The value significantly decrease from 0.29 + 0.17 nmol/mL before hemodialysis to 0.16 + 0.05 nmol/mL after hemodialysis (P.value <0.001) . Conclusion: This study confirmed that in chronic renal failure patients who are on haemodialysis, serum molybdenum level are significantly higher than normal, because the main excretion route of molybdenum is the kidney. The level of serum molybdenum was significantly decrease after hemodialysis. It is necessary massively remove molybdenum in the future with new dialysis method or with new adsorptive agent in patients requiring long term hemodialysis.